New user? Sign up

Existing user? Sign in

What will be the answer if \((2986759948578869038956)^{2}-(2986759948578869038955)^{2}\)

Note by Fahad Shihab 3 years, 12 months ago

Sort by:

\[\begin{eqnarray*}2986759948578869038956^2-2986759948578869038955^2&=&2986759948578869038956+2986759948578869038955\\&=&5973519897157738077911\end{eqnarray*}\] by difference of squares.

Log in to reply

jk

that's wrong u idiot then u multiply by (a-b)

Consider the first term \(x\) and the 2nd term as \(x-1\). Therefore,\(x^{2}-(x-1)^2=2x-1=\)\(2\) x (the first term)\(-1\) is the reqd. result.

Problem Loading...

Note Loading...

Set Loading...

## Comments

Sort by:

TopNewest\[\begin{eqnarray*}2986759948578869038956^2-2986759948578869038955^2&=&2986759948578869038956+2986759948578869038955\\&=&5973519897157738077911\end{eqnarray*}\] by difference of squares.

Log in to reply

jk

Log in to reply

that's wrong u idiot then u multiply by (a-b)

Log in to reply

Consider the first term \(x\) and the 2nd term as \(x-1\). Therefore,\(x^{2}-(x-1)^2=2x-1=\)\(2\) x (the first term)\(-1\) is the reqd. result.

Log in to reply